Communication Management As A Preliminary Step In The Citizen Participatory Process - Korti, Rafika; Sassi Boudemagh, Souad (جامعة الوادي - University of Eloued, 2021)
Through this article, we present the process of evaluating the degree of communication management in the elaboration of permanent safeguard plan's projects in Algeria, by applying the Arneisten scale. This evaluation was carried out on three different projects which selected at different stages of their life cycle: first one is the case of Constantine and Ghardaïa (have been acheived) and the second is the case of El-Oued (is in progress). The methodology followed to accomplish this evaluation is presented synthetically in the first part of the article, followed by the presentation and discussion of the results obtained using the SPSS statistical software in the second part.
مقال
Keywords: Permanent Safeguard Plan ; Communication Management ; evaluation ; Citizen Participatory Process